2022
DOI: 10.34172/jrcm.2022.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of winter sports injuries: A prospective single center study

Abstract: Background: This study aimed to present the epidemiological and clinical effects of skiing training and use of protective equipment on skiing, sledding and snowboarding injuries. Methods: The patients were evaluated in two groups according to both their skiing experience and use of protective equipment. The characteristics of the patients, such as age, gender, injury area, and injury type were statistically evaluated according to the groups. Results: A total of 191 patients, 68 (35.6%) female and 123 (64.4%) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…[18] In another study, Gür et al determined that 55% of patients with winter sports injuries were diagnosed with soft tissue trauma and 33.5% with fractures. [15] In the current study, similar to the literature, soft tissue trauma was the most common diagnosis, followed by bone fractures.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[18] In another study, Gür et al determined that 55% of patients with winter sports injuries were diagnosed with soft tissue trauma and 33.5% with fractures. [15] In the current study, similar to the literature, soft tissue trauma was the most common diagnosis, followed by bone fractures.…”
Section: Discussionsupporting
confidence: 81%
“…[13] In a study conducted by Gür et al, the rates of upper and lower extremity injuries were determined as 31.9% and 30.9% respectively among individuals engaging in winter sports. [15] In our study, the most orthopedic injury localization was found to be the lower extremity, and the most common site of injury was the knee.…”
Section: Discussionmentioning
confidence: 57%